Policy Making Implementation Studies from Papua New Guinea - May, Ron (Studies in State and Society in the Pacific, 2009)
There is a vast literature on the principles of public administration and good governance, and no shortage of theoreticians, practitioners and donors eager to push for public sector reform, especially in less-developed countries. Papua New Guinea has had its share of public sector reforms, frequently under the influence of multinational agencies and aid donors. Yet there seems to be a general consensus, both within and outside Papua New Guinea, that policy making and implementation have fallen short of expectations, that there has been a failure to achieve 'good governance'. This volume, which brings together a number of Papua New Guinean and Australian-based scholars and practitioners with deep familiarity of policy making in Papua New Guinea, examines the record of policy making and implementation in Papua New Guinea since independence. It reviews the history of public sector reform in Papua New Guinea, and provides case studies of policy making and implementation in a number of areas, including the economy, agriculture, mineral development, health, education, lands, environment, forestry, decentralization, law and order, defence, women and foreign affairs, privatization, and AIDS. Policy is continuously evolving, but this study documents the processes of policy making and implementation over a number of years, with the hope that a better understanding of past successes and failures will contribute to improved governance in the future.